Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/ana.24907
|View full text |Cite
|
Sign up to set email alerts
|

Olig1 is required for noggin‐induced neonatal myelin repair

Abstract: Objective Neonatal white matter injury (NWMI) is a lesion found in preterm infants that can lead to cerebral palsy. Although antagonists of bone morphogenetic protein (BMP) signaling, such as Noggin, promote oligodendrocyte precursor cell (OPC) production after hypoxic-ischemic injury, the downstream functional targets are poorly understood. The bHLH protein Olig1 promotes oligodendrocyte (OL) development and is essential during remyelination in adult mice. Here, we investigated whether Olig1 function is requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…To answer the second question, we used mathematical algorithms to explore five potential gene biomarkers (Tk1, Cyr61, Olig1, Slc6a9, and Pcolce2), considering the impact of both SAH and LCN2 treatment at different time points, and also used the manually reviewed experimental evidence to demonstrate that Cyr61 (Yu et al, 2018), Olig1 (Sabo et al, 2017), and Slc6a9 (Huang et al, 2016) were closely related to SAH. Although Tk1 and Pcolce2 have not been reported to be associated with SAH, we will investigate their connections in future work.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To answer the second question, we used mathematical algorithms to explore five potential gene biomarkers (Tk1, Cyr61, Olig1, Slc6a9, and Pcolce2), considering the impact of both SAH and LCN2 treatment at different time points, and also used the manually reviewed experimental evidence to demonstrate that Cyr61 (Yu et al, 2018), Olig1 (Sabo et al, 2017), and Slc6a9 (Huang et al, 2016) were closely related to SAH. Although Tk1 and Pcolce2 have not been reported to be associated with SAH, we will investigate their connections in future work.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrate that LCN2 (Warszawska et al, 2013) can effectively intervene in or treat SAH from a cell signaling pathway perspective. Also, three key genes were identified and validated by manual review of the experimental evidence (Huang et al, 2016;Sabo et al, 2017;Yu et al, 2018). Finally, the results showed that the ensemble learning model performed better for early SAH prediction than the classical LR, SVM, and Naive-Bayes models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, they found that elevated levels of transforming growth factor-β (TGF-β) were produced in the H-I brain and that the aberrant levels of GFAP in the SVZ could be reduced by administering an antagonist to the TGF-β receptor, activin-like kinase receptor-5 (65). In a recent study by Sabo et al (66), they found evidence for increased bone morphogenetic protein signaling in Olig1+ SVZ cells, which correlated with decreased production of oligodendrocytes and increased production of interneurons (66).…”
Section: Prospects For Repair and Cell Replacement After Perinatal H-imentioning
confidence: 99%